2009
DOI: 10.1080/00140130902752118
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimal size for posture categories used in video-based posture assessment methods

Abstract: Currently, there are no standards for the development of posture classification systems used in observation-based ergonomic posture assessment methods. This study was conducted to determine if an optimal posture category size for different body segments and posture views could be established by examining the trade-off between magnitude of error and the number of posture category misclassification errors made. Three groups (trunk flexion/extension and lateral bend; shoulder flexion/extension and adduction/abduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Allowing axial rotation of the manikin appeared to be useful as Table 1 showed that those rotations were much larger than the out of plane motions of the trunk in the present study, and did not negatively affect the accuracy. A last source of errors that we aimed to overcome with the present method is the error made by crude categorization of segment orientations (de Looze et al, 1994;van Wyk et al, 2009), since matching of body orientations can be performed on a continuous scale.…”
Section: Discussionmentioning
confidence: 99%
“…Allowing axial rotation of the manikin appeared to be useful as Table 1 showed that those rotations were much larger than the out of plane motions of the trunk in the present study, and did not negatively affect the accuracy. A last source of errors that we aimed to overcome with the present method is the error made by crude categorization of segment orientations (de Looze et al, 1994;van Wyk et al, 2009), since matching of body orientations can be performed on a continuous scale.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that these patients present with maladaptive spinal postures and movement patterns that expose their spines to increased loads and strain (O'Sullivan 2005). In line with this, spinal posture is considered by many in both clinical practice and research to be a factor in the development and maintenance of LBP (van Dillen et al 2003b, Poitras et al 2005, Dankaerts et al 2006a, Womersley and May 2006, van Wyk et al 2009. A number of studies now support the existence of these altered spinal postures in subjects with NSCLBP when examined in a laboratory environment (Burnett et al 2004, Dankaerts et al 2006a,b, 2009, Womersley and May 2006, Smith et al 2008) and modification of posture has been associated with improved clinical outcomes (van Dillen et al 2003a, Dankaerts et al 2007).…”
Section: Introductionmentioning
confidence: 88%
“…For example, Bao and colleagues (2009) reported that 30 intervals provided better agreement among the raters compared to postures coded with 10 intervals. Others have also found that the optimal size of posture categories can range between 15 and 30 , depending on the body segment (van Wyk et al, 2009). In fact, some have reported that observers are able to code dichotomous postures and other gross categories of posture with very high reliability and methodological validity (Kilbom, 1994).…”
Section: Selection Of Postural Variablesmentioning
confidence: 99%